Optimal Wells turbine speeds at different wave conditions. (December 2016) - Halder, Paresh; Samad, Abdus
Highlights: A relationship has been demonstrated between the turbine speed and air velocity. The cases with and without casing treatment have been optimized and optimal speed–velocity relationships were obtained. Grooved turbine performs better and detailed flow analysis explains the reason. Abstract: The present study aims to predict and optimize the operating range of a Wells turbine that essentially works on the principle of bidirectional flow in an ocean renewable energy system. The turbine operates in a narrow range because of variability in waves, machine geometry and low incidence angle that lead to stumpy performance of the turbine. Hence, a relationship between the fluid velocity and the turbine speed has been established to design a turbine with higher performance. The two different cases, with and without a tip groove, were considered to predict the optimal turbine speed for the different flow velocities. A multiple-surrogate based approach has been used to find correlation between the turbine speed and the air velocity, and a Reynolds-averaged Navier–Stokes equation solver evaluated the turbine performance parameters. Furthermore, several combinations of the variables (flow velocity and turbine speed) along with an objective function (efficiency) were evaluated by the solver. The grooved-casing design performs better than that of the without grooved-casing, and the mid-chord of the blade enhances the exchange of momentum among different directions and suppresses the unsteadiness.